Thermal Analysis of Whole Bacterial Cells Exposed to Potassium Permanganate Using Differential Scanning Calorimetry: a Biphasic Dose-Dependent Response to Stress - Marina K. Abuladze; Victor M. Sokhadze; Emma N. Namchevadze; E. Kiziria; Leila V. Tabatadze; Lia V. Lejava; Sh. Gogichaishvili; Nugzar B. Bakradze (The Scientific World Journal)
Differential scanning calorimetry (DSC) was applied to estimate the impact of the toxic oxidant potassium permanganate (PM) on the intracellular structural and functional alterations at whole cell level using soil bacteria Arthrobacter oxydans as a model culture. Differential scanning calorimetry (DSC) was applied in order to estimate the impact of the toxic oxidant potassium permanganate (PM) on the intracellular structural and functional alterations at the whole cell level using the soil bacteria Arthrobacter oxydans as a model culture. We compared the total melting heat and the temperature of DNA-protein complex (DNP) melting at the PM application prior to the calorimetry measurement and after 24-h exposure at the concentration range 0.02–1.4 mM. The initial oxidative effect caused changes in the pattern of the whole cell melting spectra (mainly at the temperature range 56–78°C), the decrease of Tmax °C DNP melting, and did not influence significantly the total heat of bacterial melting at different concentrations of PM. The prolonged effect of permanganate up to 24 h was characterized by a biphasic dose-dependent response to stress estimated by the DSC technique and the colony-forming assay. The low doses of PM (0.02 and 0.2 mM) stimulated cell proliferation, and increased the total whole cell melting heat and the temperature of DNP melting. The toxic effect of PM up to 0.04 mM reduced cell viability, changed the character of multipeaked thermograms, and lowered the total melting heat and the temperature of DNP melting in a concentration-dependent manner. This study presents the DSC method for evaluating and monitoring the effects of exposure to potential human and environmental toxicants.